The gut microbiome in solid organ transplantation - Baghai Arassi, Maral; Zeller, Georg; Karcher, Nicolai; Zimmermann, Michael; Tönshoff, Burkhard (Pediatric transplantation, 2020)
Despite ground-breaking advances in allogeneic transplantation, allograft rejection and immunosuppressant-specific complications remain a major challenge in transplant medicine. Growing evidence suggests the human gut microbiome as a potential contributor to transplant outcome and patient health.
First published: 30 September 2020
Gesehen am 06.12.2021